PICARESQUE NOVELS IN CANNERY ROW, CANDIDE OR OPTIMISM, AND DON QUIJOTE - Muhamad Ghifari Muharam; Tenny Sudjatnika; Pepen Priyawan (Saksama: Jurnal Sastra, 2022)
The research compared rascals in three Picaresque novels: Cannery Row, Candide or Optimism, and Don Quijote. It used Picaresque theories from Clarence Hugh Holman (1972), as well as Gustavo Pellon and Julio Rodriguez-Luis (1986), that specified rascal or rogue. This understanding explains how some Picaresque novels feature rascal characters who are silly, stupid, reckless, rude and have other negative traits, but they also have qualities of kindness, a good heart, and attentiveness hidden behind them. Mack and the boys, Candide, and Don Quijote are all depicted as rogues. The Picaresque element is used as a formula in the story to determine and exemplify rascal values. The researcher stated two problems related to Picaresque rascal: what are the similarities between Picaresque rascals in Cannery Row, Candide or Optimism, and Don Quijote? In addition, the purpose of this research is to identify Picaresque rascals in three objects. Furthermore, this research utilizes Ian Dey's (1993) literary criticism method, namely qualitative analysis. It is used to decipher the data of each object one by one and to obtain information about the Picaresque. The researcher then used Susan Bassnett's (1999) comparative method to compare topics. The similarities between the three objects are the results of this research. The similarities are rascals, education, instability of personality, criminality, and themes.Â Â Keywords: Comparative Literature 1; Elements 2; Novel 3; Picaresque 4; Rascal 5